A methodology for the selection and characterization of riboflavin-overproducing Weissella cibaria strains after treatment with roseoflavin - Diez-Ozaeta, Iñaki; Martín-Loarte, Lucía; Mohedano, Mari Luz; Tamame, Mercedes; Ruiz-Masó, José Ángel; del Solar, Gloria; Dueñas, María Teresa; López, Paloma (Frontiers in Microbiology, 2023)
Fermentative processes by lactic acid bacteria can produce metabolites of interest to the health and food industries. Two examples are the production of B-group vitamins, and of prebiotic and immunomodulatory dextran-type exopolysaccharides. In this study, three riboflavin- and dextran-producing Weissella cibaria strains (BAL3C-5, BAL3C-7 and BAL3C-22) were used to develop a new method for selection and isolation of spontaneous riboflavin-overproducing W. cibaria mutants. This method was based on the selection of strains resistant to roseoflavin. The DNA sequencing of the FMN riboswitch of bacterial cell populations treated with various roseoflavin concentrations, revealed the existence of at least 10 spontaneous and random point mutations at this location. Folding and analysis of the mutated FMN riboswitches with the RNA fold program predicted that these mutations could result in a deregulation of the rib operon expression. When the roseoflavin-treated cultures were plated on medium supporting dextran synthesis, the most promising mutants were identified by the yellow colour of their mucous colonies, exhibiting a ropy phenotype. After their isolation and recovery in liquid medium, the evaluation of their riboflavin production revealed that the mutant strains synthesized a wide range of riboflavin levels (from 0.80 to 6.50 mg/L) above the wild-type level (0.15 mg/L). Thus, this was a reliable method to select spontaneous riboflavin-overproducing and dextran-producing strains of W. cibaria. This species has not yet been used as a starter or adjunct culture, but this study reinforces the potential that it has for the food and health industry for the production of functional foods or as a probiotic. Furthermore, analysis of the influence of FMN present in the growth medium, on rib mRNA and riboflavin levels, revealed which mutant strains produce riboflavin without flavin regulation. Moreover, the BAL3C-5 C120T mutant was identified as the highest riboflavin-overproducer. Determination of the chromosomal DNA sequence and that of BAL3C-5, revealed a total identity between the 2 strains except for the C120T mutation at the FMN riboswitch. To our knowledge, this work is the first demonstration that only a single alteration in the genome of a lactic acid bacteria is required for a riboflavin-overproducing phenotype.